DAMPAK PENGGUNAAN INSTAGRAM TERHADAP ETIKA KEWARGANEGARAAN DI INDONESIA - Juliani, Aisya; Sulistyarini, Sulistyarini; Dewantara, Jagad Aditya (Universitas Tanjungpura, 2025)
The rapid growth of Instagram as a social media platform has significantly influenced social interactions, particularly among young people in Indonesia. While it serves as a space for self-expression, learning, and digital activism, its impact on civic ethics remains a critical concern. This study aims to analyse the influence of Instagram usage on civic ethics among Indonesian youth. Employing a mixedmethods approach, the research integrates quantitative data from a survey of 300 respondents aged 17 to 30 across five major cities